Accounting for microfinance failure: insights from Zambia. (1st January 2013) - Siwale, Juliana; Ritchie, John
The global trials of mainstream finance have brought calls for the development of human scale alternatives such as microfinance. However, developing country microfinance has itself been taken to task over its collective failings without much evidence about individual grassroots microfinance institution (MFI) failure. So, using an extended case study of PRIDE Zambia (PZ), this paper examines different stakeholder and other accounts about how this once promising MFI frontier failed. It finds that fast track founding and premature expansion based upon indifferent governance, hierarchical mismanagement, and unrecognised frontline problems further compounded by malpractice and corruption were central to PZ's final failure. Zambia is a difficult frontier for donor-funded MFIs and, when PZ first sought to change its original grassroots character, its survival was so jeopardised that it failed as a result.